Pengaruh Kompetensi Spiritualitas Guru Pendidikan Agama Kristen Terhadap Karakter Siswa kelas VIII SMP Negeri 3 Tarutung Kabupaten Tapanuli Utara Tahun Pembelajaran 2023/2024 - Andrian Purba; Ronny Simatupang; Maria Widiastuti; Rusmauli Simbolon; lince R.T Simamora (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2024)
The research aims to determine the positive and significant influence of the spiritual competence of Christian Religious Education teachers on the character of class VIII students at SMP Negeri 3 Tarutung for the 2023/2024 academic year. The research hypothesis is that there is a positive and significant influence between the spiritual competence of Christian Religious Education teachers on the character of class VIII students at SMP Negeri 3 Tarutung for the 2023/2024 academic year.Descriptive and inferential quantitative research methods. The population of all class VIII students at SMP Negeri 3 Tarutung for the 2023/2024 academic year who are Protestant Christians is 163 people. Random sampling was taken, namely 25% of the total population, namely 41 people. The research instrument is a closed questionnaire. The results of data analysis obtained: a) The value rcount=0.625>rtabel=0.308 and tcount=5,000>ttable=2.021 shows that there is a positive and significant relationship between the spiritual competence of Christian Religious Education teachers and the character of class VIII students at SMP Negeri 3 Tarutung for the 2023 Academic Year/ 2024. b) Regression equation. c) The determination test revealed that the influence was 39.06%. d) Hypothesis testing obtained Fcount=25.078>Ftable=3.23, so H0 is rejected and Ha is accepted. The research concluded that there was a positive and significant influence between the spiritual competence of Christian Religious Education teachers on the character of class VIII students at SMP Negeri 3 Tarutung for the 2023/2024 academic year.